Wacana Tata Kelola Kebencanaan: Kajian Pembicaraan Aktor Melalui Analisis Media Sosial Twitter - Sapto Setyo Nugroho; Daniel Pasaribu (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2022)
This paper examines the discourse on disaster governance issues in Indonesia. By focusing on discourse analysis, disaster studies can be viewed with a social science perspective and with a discursive governance approach. This paper is also an alternative to the dominant concept of "disaster management" in the previous studies. The study was conducted by searching for primary data on one keyword, namely "Penanggulangan Bencana" on Twitter with Netlytic application – social media text and social network analyzer. Through schemes of text analysis, social cognition and social analysis, the results of data collection and analysis show the dominance of speech and the role of government and the diverse significance of other actors. This discusses the unorganized "double track policy-making" model and disaster-conscious behavior through an internalized "living with disaster" view.